If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+x+1+x+2=66
We simplify the equation to the form, which is simple to understand
x+x+1+x+2=66
We move all terms containing x to the left and all other terms to the right.
+1x+1x+1x=+66-1-2
We simplify left and right side of the equation.
+3x=+63
We divide both sides of the equation by 3 to get x.
x=21
| 12w-19w=56 | | 125x-5x^3=0 | | 125-5x^3=0 | | (m-3)(m+3)-(m+7)(m+7)= | | 8(x+8)-21= | | 11(5a)= | | 2x-5x+7x-8x= | | 8(t-2)=3(t-9) | | 3k=(-0.857142) | | -13r+10=5r-46 | | 4w-9=0 | | 20x+2=5(4x+1)-x+5 | | 10y=-5y | | 0.33(p+1)=0.5(p-2) | | 5x+11=51 | | x=7x | | n*5-10=-25 | | 3x-48x=0 | | 7m+49= | | (r-5)=-6 | | 23=2x | | (2y-3)(y+5)=0 | | y=1.5x-1 | | 25x+3=5(5x+1)-x+4 | | x+3x^2-2=0 | | y=-3.5x-2 | | y=3.5x-1 | | y=6x^2-9 | | (-8x)-4=36 | | 5=3x-4 | | 2=4m+8 | | -19=3x-4 |